2021
DOI: 10.3389/fcimb.2021.737204
|View full text |Cite
|
Sign up to set email alerts
|

Active Smoking Induces Aberrations in Digestive Tract Microbiota of Rats

Abstract: Cigarette smoking could have certain effects on gut microbiota. Some pioneering studies have investigated effects of active smoking on the microbiome in local segments of the digestive tract, while active smoking-induced microbiome alterations in the whole digestive tract have not been fully investigated. Here, we developed a rat model of active smoking and characterized the effects of active smoking on the microbiota within multiple regions along the digestive tract. Blood glucose and some metabolic factors l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Turicibacter is a common genus of Firmicutes, which is closely related to lipid and carbohydrate metabolism. As a potential beneficial genus, studies showed that Turicibacter protects the host from chronic and inflammatory diseases (Wang et al, 2021b). Based on these aforementioned findings, we speculated that the mechanism of CMHD granules is related to the alternation of the microbiota structure and some specific microbiota in the intestine.…”
Section: Discussionmentioning
confidence: 88%
“…Turicibacter is a common genus of Firmicutes, which is closely related to lipid and carbohydrate metabolism. As a potential beneficial genus, studies showed that Turicibacter protects the host from chronic and inflammatory diseases (Wang et al, 2021b). Based on these aforementioned findings, we speculated that the mechanism of CMHD granules is related to the alternation of the microbiota structure and some specific microbiota in the intestine.…”
Section: Discussionmentioning
confidence: 88%
“…Regarding its impact on metabolism, smoking has been related to glucose and lipid disorders [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the ratio of cholic acid (CA) to chenodeoxycholic acid (CDCA) was significantly reduced in the liver of mice exposed to cigarette smoke [ 64 ]. Furthermore, smoking induced hyperglycemia and significant reductions in serum insulin and leptin levels [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…No DA genera associated with CIG status were found in the original, ComBat-seq, MMUPHin, Percentile, or ConQuR-libsize corrected data (adjusting for HPV status, race, and sexual orientation). In the ConQuR-corrected data, Coprococcus and 1-68 (Tissierellaceae) (adjusted p values < 0.0001, =0.0071) were identified, where Coprococcus has been shown to be significantly decreased by active smoking 42 .…”
Section: Application To a Single Study With A Large Key Variable Effe...mentioning
confidence: 99%